ANALISIS SISTEM JARINGAN AIR BERSIH PERUMDAM TIRTA SENENTANG PADA UNIT TANJUNG PURI KABUPATEN SINTANG - Apri Ananda Putra; Stefanus Barlian Soeryamassoeka; Henny Herawati (UKI Press, 2023)
The requirement for clean water in Sintang Regime, particularly served by Perumdam Tirta Senentang Tanjung Puri unit, is expanding step by step alongside the rising populace. The motivation behind this study is to get the aggregate sum of water request served and get the consequences of the dispersion network condition examination until 2037. To decide the accessibility of Kapuas Stream water, the False technique and dissemination network reenactment investigation utilizing the Epanet 2.2 program were utilized. How much pinnacle hour water interest in 2022 is 29,31 liters/second and in 2037 is 56,09 liters/second. Examination of the circulated water request network in existing circumstances in 2022 there is a speed that has not met the prerequisites with the least worth of 0,06 m/second and the most elevated worth of 0,88 m/second. Besides, an extra release was completed in 2037 circumstances, it was found that few lines didn't meet the prerequisites, in particular the least headloss unit worth of 0,21 m/km and the most noteworthy of 15,44 m/km, while the least speed esteem was 0,11 m/second and the most elevated was 1,69 m/second. In the wake of supplanting the line distance across in 2037, pressure results and headloss units that meet the prerequisites are acquired. Nonetheless, there are a few lines with speed esteems that don't meet the prerequisites, the least worth is 0,11 m/second and the most noteworthy worth is 0,95 m/second. This shows that the state of the spotless water circulation organization can in any case be grown so that administrations can be more ideal. Keywords: Clean Water Network Distribution; Epanet 2.2; the need for clean water; mock method; Perumdam Tirta Senentang; Kapuas River